Key trends purposes of education in ukraine - Кирда, А.Г. (Proceedings of National Aviation University (archive), 2006)
The article is devoted to the analysis of purpose progressing in the education of Ukraine /the second half of the XX – beginning of the XXI century: from goal defining at the national level in plans and acts to the objective concretizing by secondary and higher schools. Major tendencies and stages of educational purpose evolution are determined and described.